Surfactant protein (SP)-A suppresses preterm delivery and inflammation via TLR2. - Varkha Agrawal (PLoS ONE, 2013)
Toll like receptors (TLRs) are pattern-recognition molecules that initiate the innate immune response to pathogens. Pulmonary surfactant protein (SP)-A is an endogenously produced ligand for TLR2 and TLR4. SP-A has been proposed as a fetally produced signal for the onset of parturition in the mouse. We examined the effect of interactions between SP-A and the pathogenic TLR agonists lipopolysaccharide (LPS), peptidoglycan (PGN) and polyinosinic:cytidylic acid (poly(I:C)) (ligands for TLR4, TLR2 and TLR3, respectively) on the expression of inflammatory mediators and preterm delivery. Three types of mouse macrophages (the cell line RAW 264.7, and fresh amniotic fluid and peritoneal macrophages, including macrophages from TLR4 and TLR2 knockout mice) were treated for up to 7 hours with pathogenic TLR agonists with or without SP-A. SP-A alone had no effect upon inflammatory mediators in mouse macrophages and did not independently induce preterm labor. SP-A significantly suppressed TLR ligand-induced expression of inflammatory mediators (interleukin (IL)-1β, tumor necrosis factor (TNF)-α and the chemokine CCL5) via a TLR2 dependent mechanism. In a mouse inflammation-induced preterm delivery model, intrauterine administration of SP-A significantly inhibited preterm delivery, suppressed the expression of proinflammatory mediators and enhanced the expression of the CXCL1 and anti-inflammatory mediator IL-10. We conclude that SP-A acts via TLR2 to suppress TLR ligand-induced preterm delivery and inflammatory responses.